An Elusive Diagnosis of Castleman Disease - Yasmine Rifai, BA; Rohun Bhagat, MD; Sudish Murthy, MD, PhD; Alejandro Bribriesco, MD (Annals of Thoracic Surgery Short Reports, 2024)
We present the case of a 41-year-old man with an anterior mediastinal mass and constellation of clinical symptoms, including dyspnea, pleural effusions, pericardial effusions, renal insufficiency, and pancytopenia. After inconclusive results on several laboratory tests and a nondiagnostic surgical biopsy specimen, a specimen from a second surgical biopsy identified the patient’s condition as Castleman disease associated with TAFRO (thrombocytopenia, anasarca, fevers, reticulin myelofibrosis, organomegaly) syndrome. This case highlights the importance of obtaining large tissue biopsy samples, interval follow-up, and acknowledging cognitive biases.